MODEL PENDAMPINGAN MAHASISWA BIDANG KEAGAMAAN DALAM KEPENULISAN ARTIKEL ILMIAH - Hidayatul Fikra; Wahyudin Darmalaksana (UIN Sunan Gunung Djati Bandung, 2021)
This study aims to formulate a model for assisting in writing articles and scientific publications for students in the field of religion. This study uses a qualitative approach withdescriptiveanalytical methods. The results of this study indicate that the model of mentoring students in the field of religion in article writing was effective, resulting in 279 scientific publications throughout 2020-2021. The discussion of the research results reveals that strategic planning by applying a logical framework thatis operatedproperly has played a role in forming an effective mentoring model for developing student skills in the field of religion in writing articles toachievingpublication in scientific journals. The conclusion of this study is that the model of mentoring students in the field of religion works effectively in achieving article writing and scientific publications. This study recommends the application of the mentoring model with continuous testing through developmentof Islamicreligious higher education institutions.